23 VAGUS NERVE ACTIVITY AND CYTOKINE RESPONSIVENESS IN PATIENTS WITH RHEUMATOID ARTHRITIS. (1st March 2006) - Goldstein, R. S.; Bruchfeld, A. N.; Gallowitsch-Puerta, M.; Patel, N.; Yang, H.; Rosas-Ballina, M.; Lee, D. C.; Czura, C. J.; Sama, A. E.; Tracey, K.J.
Abstract : Recent literature has shown that the central nervous system can modulate the innate immune response through a rapid, local, and integrated mechanism. This pathway, termed the cholinergic anti-inflammatory pathway (CAP), acts via the vagus nerve through the neurotransmitter acetylcholine (Tracey, 2002). Activation of this pathway results in decreased proinflammatory cytokine production in in vitro experiments and in vivo models of inflammatory disease (Borovikova et al, 2000; Bernick et al, 2002). It has been observed that autonomic dysfunction develops in patients with diseases associated with cytokine excess, such as sepsis and rheumatoid arthritis (RA) (Hakala M and RK Niemela, 2000; Louthrenoo et al, 1999). However, the relationship between autonomic dysfunction and cytokine synthesis has not been explored. The purpose of this study is to explore the relationship between vagus nerve activity and cytokine synthesis in patients with RA compared to healthy subjects. A prospective observational study was performed at the North Shore-LIJ GCRC in subjects with RA and age- and sex-matched healthy volunteers ( n = 12, 50 ± 10.9 years, n = 13, 42 ± 14.6, respectively). Vagus nerve activity was assessed by determining instantaneous heart rate variability (HRV) using parameters representing vagal nerve activity, including high-frequency power (HF), SDANN, and RMSSD. Blood was collected and stimulated with endotoxin and subsequently analyzed for the cytokines tumor necrosis factor (TNF) and high mobility box 1 protein (HMGB1). All measured components of HRV were attenuated in the RA subjects as compared to the healthy volunteers (HF power [msec 2 ] = 40 ± 8.8, 410 ± 122, p < .01, SDANN = 32 ± 4.5, 68 ± 12.9, p < .05, and RMSSD = 21 ± 0.41, 57 ± 11.1, p < .01, respectively). Cytokine analysis measuring serum TNF levels were attenuated in the RA group as compared to healthy volunteers (TNF [pg/mL] = 6, 474 ± 2, 028, 15, 489 ± 1, 514, p < .01, respectively). This supports our hypothesis that autonomic dysfunction, as reflected by lower vagal nerve output, may contribute to underlying dysfunctional cytokine activity during chronic inflammation. (Data presented as mean ± standard error and analyzed by two-tailed Student's t-test.) Supported by NIGMS and GCRC M01RR018535 of The Feinstein Institute for Medical Research, North Shore-LIJ Health System.